An update on paediatric respiratory diseases. (6th April 2018) - Epaud, Ralph
During the 2017 European Respiratory Society International Congress in Milan, Italy, exciting topics on childhood lung disease were reviewed in the session "Paediatric year in review: update on paediatric pulmonology". These brief reviews highlighted publications in the field of paediatric lung disease and were presented by well-known experts within the field. An update of paediatric lung diseases including interstitial lung disease, virus causing wheezing disorders and diaphragmatic hernia together with new imaging diagnosis tools http://ow.ly/TclX30iZazK